2022
DOI: 10.1155/2022/9449427
|View full text |Cite|
|
Sign up to set email alerts
|

Difficulties in the Treatment of Diabetic Foot and Research Progress of Combination of Traditional Chinese and Western Medicine

Abstract: A diabetic foot is any disorder directly attributable to peripheral arterial disease (PAD) and/or the sensory neuropathies influencing the diabetic foot; it is a long-term (or “chronic”) complication of diabetes. Generally, it is a permanent (or “chronic”) comorbidity of diabetes. The swallowing of peripheral neuropathy and peripheral vascular disease leads to damage to the soft tissue, bone, and joint system of the foot. In addition, diabetic feet are also susceptible to infection, which can lead to lameness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Given the patient's high lipid levels, we gave her atorvastatin for lipid regulation and plaque stabilization, and aspirin for antiplatelet coagulation as a routine treatment. Western medicine has been shown to have certain efficacy in the treatment of diabetic foot, however, there is increasing evidence that the combination of Chinese and Western medicine is more effective in treating diabetic foot [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the patient's high lipid levels, we gave her atorvastatin for lipid regulation and plaque stabilization, and aspirin for antiplatelet coagulation as a routine treatment. Western medicine has been shown to have certain efficacy in the treatment of diabetic foot, however, there is increasing evidence that the combination of Chinese and Western medicine is more effective in treating diabetic foot [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It causes great pain and economic pressure to the patient, and also brings a heavy burden to the patient’s family, the medical industry and even society ( 4 ). Traditional Chinese medicine (TCM) has a variety of methods for the treatment of diabetic foot with obvious advantages, which can be divided into internal treatment and external treatment of TCM ( 5 ). External treatment of traditional Chinese medicine refers to the treatment of skin (mucous membrane) or from outside the body with drugs, manipulations, or instruments under the guidance of traditional Chinese medicine theory.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The external treatment of traditional Chinese medicine (TCM) includes acupuncture, massage, and acupoint application, which has a very good effect on DPVD and is safer. [11] According to ancient TCM records, acupuncture, massage, acupoint application, and other treatments can promote blood circulation and improve nerve function. [12,13] Previous randomized controlled trials (RCTs) have confirmed the effectiveness of external TCM therapy in the treatment of DPVD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] The external treatment of traditional Chinese medicine (TCM) includes acupuncture, massage, and acupoint application, which has a very good effect on DPVD and is safer. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%